2021
DOI: 10.3389/fpsyg.2021.753551
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Cognitive, Language, and Motor Delays for Low-Income Preterm Infants: A Brazilian Cohort Longitudinal Study on Infant Neurodevelopment and Maternal Practice

Abstract: Aim: This study examined the neurodevelopment trajectories, the prevalence of delays, and the risks and protective factors (adverse outcomes, environment, and maternal factors) associated with cognitive, motor, and language development for preterm infants from 4– to 24-months.Method: We assessed 186 preterm infants (24.7% extremely preterm; 54.8% very preterm; 20.4% moderate/late preterm) from 4– to 24-months using the Bayley Scales of Infant Development – III. Maternal practices and knowledge were assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…Belfort et al 57 found that, in infants below 30 weeks of GA, breastmilk intake in the first 28 days of life was associated with greater brain deep nuclear grey matter at term equivalent age, and better motor and cognitive performance at 7 years of age. However, these findings were not replicated by subsequent studies, 55,58 which did not identify any feeding associated differences in the achievement of motor milestones in very preterm infants. Our study found that, adjusting for maternal age, smoking in pregnancy, and SES index, maternal milk feeding at discharge from the neonatal unit was associated with lower DCD risk, particularly overall and in the Fine Motor/Handwriting domains.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Belfort et al 57 found that, in infants below 30 weeks of GA, breastmilk intake in the first 28 days of life was associated with greater brain deep nuclear grey matter at term equivalent age, and better motor and cognitive performance at 7 years of age. However, these findings were not replicated by subsequent studies, 55,58 which did not identify any feeding associated differences in the achievement of motor milestones in very preterm infants. Our study found that, adjusting for maternal age, smoking in pregnancy, and SES index, maternal milk feeding at discharge from the neonatal unit was associated with lower DCD risk, particularly overall and in the Fine Motor/Handwriting domains.…”
Section: Discussionmentioning
confidence: 64%
“…As with other developmental outcomes, 54 we found that socio‐economic variables such as maternal age, smoking in pregnancy, parental education, and occupational profession may be important in shaping the neuropsychological profile of a child, and in our study were associated with risk of motor problems even when controlling for biomedical factors. The root of these relations may be both socio‐economic and educational, linked to the level of home affordances, 30 opportunities for motor activities, training, and outdoor leisure time, as well as to more active parenting practices and stimulating environment 55 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations